'VT Sweet': A vegetable soybean cultivar for commercial edamame production in the mid‐Atlantic USA. Issue 1 (26th October 2021) - Zhang, Bo; Lord, Nilanka; Kuhar, Thomas; Duncan, Susan; Huang, Haibo; Ross, Jeremy; Rideout, Steven; Arancibia, Ramon; Reiter, Mark; Li, Song; Chen, Pengyin; Mozzoni, Leandro; et al.
Abstract: Commercially viable cultivars adapted to U.S. production regions that meet consumer acceptance criteria are desperately needed by the growing domestic edamame industry. Here, we report the development and release of 'VT Sweet' (Reg. no. CV‐542, PI 699062), the first vegetable soybean [ Glycine max  (L.) Merr.] cultivar released by Virginia Tech. VT Sweet is a late maturity group (MG) V cultivar (relative maturity 5.6, 129 d to harvest) with determinate growth habit, purple flowers, gray pubescence, tan pod wall, and yellow hila. VT Sweet has superior characteristics for edamame such as large pod size (13.9 g/10 pods; 40.4 mm long, 11.4 mm wide, and 7.6 mm thick) and low one‐bean pod proportion (15%), as well as low pod pubescence density (359 hairs/2.4 cm 2 ). VT Sweet also showed high overall consumer acceptability (6.0 ± 1.7; 9 = like extremely) and favorable tolerance to native pests. When compared with the commercial edamame check 'UA Kirksey', VT Sweet showed 102% of the check yield, a higher average field emergence rate (74.9 vs. 68.1%), and comparable consumer acceptability (6.05 vs. 6.10). Therefore, VT Sweet is an ideal cultivar for growers who are interested in commercial edamame production in the mid‐Atlantic region of the United States.